Electric railways 1880-1990 - Duffy, M. C. (Michael C.) (Institution of Engineering and Technology, 2003)
This book explores the history of the integration of both electric and diesel-electric railway systems and identifies the crucial role that diesel-electric traction played in the development of wireless electrification. The evolution of electrical technology and modern railway produced innovation in engineering that were integral to the development of traction power and signalling system. The book presents a thorough survey of electric railways development from the earliest days of the London underground to modern electrified main line train. The distinction between enforce electrification and economic electrification is also discussed and the pioneering role of J.J. Heilman assessed. Developed from many years of research into railway engineering topics covered include signalling and communication, power supplies and a devoted survey of traction systems, both AC and DC. The introduction test of mercury arc rectifier and lateral power semiconductor controls is also discussed in details. The author has a long standing interest in engineering history and has written many pages on aspect of railway technology.